2018
DOI: 10.3892/ijmm.2018.3859
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers in cholestasis and the therapeutic effect of melatonin by metabolomics, multivariate data and pathway analyses

Abstract: The present study investigated the anti-cholestatic effect of melatonin (MT) against α-naphthyl isothiocyanate (ANIT)-induced liver injury in rats and screened for potential biomarkers of cholestasis. Rats were administered ANIT by intraperitoneal injection and then sacrificed 36 h later. Serum biochemical parameters were measured and liver tissue samples were subjected to histological analysis. Active components in the serum were identified by gas chromatography-mass spectrometry, while biomarkers and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
(54 reference statements)
3
11
0
Order By: Relevance
“…1F ). These results were consistent with those of previous studies by our group ( 11 , 12 ). For each group, 6 random fields of view were statistically evaluated for inflammatory lesions (examples in Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…1F ). These results were consistent with those of previous studies by our group ( 11 , 12 ). For each group, 6 random fields of view were statistically evaluated for inflammatory lesions (examples in Fig.…”
Section: Resultssupporting
confidence: 94%
“…Long-term biliary obstruction may cause liver damage, even induce biliary cirrhosis or liver fibrosis and, in severe cases, may lead to liver failure ( 25 ). In recent years, it has been indicated that oxidative stress and abnormal fatty acid metabolism may be involved in the pathogenesis of intrahepatic cholestasis ( 11 , 12 , 24 , 26 ). Previously, melatonin has been demonstrated to improve liver fibrosis and liver damage caused by various diseases through inhibiting oxidative damage ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound is also well known among researchers for adequately inducing cholestasis in rats and mice, 79,171 by specifically targeting bile duct epithelial cells followed by hepatocellular necrosis 137,172 . Chronic and recurrent exposure to ANIT via the diet resembles an experimental setting of chronic cholangitis, bile duct hyperplasia and peribiliary fibrosis 172‐174 . Moreover, mechanisms underlying peribiliary fibrosis in chronic ANIT models show similarities with other chronic cholestasis models, such as long‐term BDL and Mdr2 ‐/‐ mice 172 …”
Section: Chemical‐induced Rodent Modelsmentioning
confidence: 99%
“…This high dose of melatonin (relative to the 4-20 mg/kg doses used in mouse melatonin studies [91,92]) produced a modest reduction in serum liver enzymes and bilirubin with a less severe liver histology. The metabolomic changes in serum due to melatonin administration were unexceptional and, in part, derived metabolically from melatonin [93]. The mechanism of ANIT-induced cholestasis continues to be investigated using metabolomic tools.…”
Section: Cholestasismentioning
confidence: 99%